2023
DOI: 10.1002/cssc.202202399
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Chemical Structure of Nitrogen‐Doped Carbon Dots for Nano‐Aminocatalysis in Aqueous Media

Abstract: Amine‐rich carbon dots (NCDs) have become promising nano‐aminocatalytic platforms in organic synthesis. These nanomaterials can be effectively produced through straightforward bottom‐up approaches using inexpensive nitrogen‐containing molecular precursors as a starting material. However, to date, there is still a limited understanding of how the molecular features of these precursors affect the catalytic activity of the resulting nanoparticles. This study concerns the production of a new family of NCDs, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…[31][32][33][34] Combined with the good fluorescence properties including controllable emission spectra and a wide range of excitation spectra, high photostability, great up-conversion ability, and excellent redox properties, [35][36][37][38] CDs are easily excited by a suitable light source to reach the excited state (CDs*), which endow them can be used as photo-oxidants or photo-reductants to obtain an electron from a donor or give an electron to an acceptor as potential photocatalysts. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] For example, Kang and coworkers reported the use of CDs as photocatalysts for the selective oxidation of benzyl alcohol to benzaldehyde. [42] MacFarlane and coworkers demonstrated that sulfated CDs can photocatalyzed ring-opening reactions of epoxides with alcohols as nucleophiles and solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] Combined with the good fluorescence properties including controllable emission spectra and a wide range of excitation spectra, high photostability, great up-conversion ability, and excellent redox properties, [35][36][37][38] CDs are easily excited by a suitable light source to reach the excited state (CDs*), which endow them can be used as photo-oxidants or photo-reductants to obtain an electron from a donor or give an electron to an acceptor as potential photocatalysts. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] For example, Kang and coworkers reported the use of CDs as photocatalysts for the selective oxidation of benzyl alcohol to benzaldehyde. [42] MacFarlane and coworkers demonstrated that sulfated CDs can photocatalyzed ring-opening reactions of epoxides with alcohols as nucleophiles and solvent.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, photocatalytic organic conversion and artificial photosynthesis initiated by organic photocatalysts are promising fields among the above‐mentioned applications of nonmetal‐doped CDs [31–34] . Combined with the good fluorescence properties including controllable emission spectra and a wide range of excitation spectra, high photostability, great up‐conversion ability, and excellent redox properties, [35–38] CDs are easily excited by a suitable light source to reach the excited state (CDs*), which endow them can be used as photo‐oxidants or photo‐reductants to obtain an electron from a donor or give an electron to an acceptor as potential photocatalysts [39–57] . For example, Kang and coworkers reported the use of CDs as photocatalysts for the selective oxidation of benzyl alcohol to benzaldehyde [42] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] Besides, the higher electron affinity and electronegativity of nitrogen can also enhance the chemical reactivity of CDs. [ 29 ] Depending on the number of heteroatoms introduced into the CDs, it can be classified as single doped or codoped. And their optical and electronic properties can be adjusted by using certain types and numbers of dopant atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent literature examples demonstrated the possibility to use CNDs for the preparation of valuable organic compounds under mild operating conditions by means of classical dark or lightdriven reactivities. [6][7][8][9][10][11] Despite recent encouraging advancements in this research field, the use of CNDs as nanoorganocatalysts for the stereoselective preparation of chiral compounds remains an elusive goal. This can possibly be related to the challenging conditions used in the preparation of chiral CNDs.…”
Section: Introductionmentioning
confidence: 99%
“…Among other possible applications, CNDs can be considered as a new generation of nano‐catalysts. Indeed, recent literature examples demonstrated the possibility to use CNDs for the preparation of valuable organic compounds under mild operating conditions by means of classical dark or light‐driven reactivities [6–11] . Despite recent encouraging advancements in this research field, the use of CNDs as nano‐organocatalysts for the stereoselective preparation of chiral compounds remains an elusive goal.…”
Section: Introductionmentioning
confidence: 99%